Empowering Special Needs Children: Community Outreach for Inclusive Mathematics Education - Surya Sari Faradiba; Sunismi; Yuli Ismi Nahdiyati Ilmi; Fuat (International Journal of Community Service Learning, 2024)
This study is motivated by the low quality of mathematics learning for students with special needs caused by the need for teaching materials tailored to their needs and the limitations of teachers in using inclusive learning strategies. This study aims to analyze the effectiveness of a community service initiative designed to improve mathematics learning for students with special needs in SLB. This study used a developmental research method with a pretest-posttest design on one group of research subjects, involving teachers and students with special needs as test subjects. The program involved 20 students and 4 teachers. The results show the initiative's effectiveness in improving math education for special needs students. Data collection was conducted through observation, interviews, and questionnaires, while the instruments used included observation guidelines, interview sheets, and questionnaires for teachers and students. The collected data were analyzed using qualitative descriptive analysis techniques and paired t-tests to measure changes in teachers' understanding and skills and improvements in students' motivation and learning outcomes. This study concludes that inclusive education interventions based on special learning aids effectively overcome learning barriers for students with special needs. The implication of this study is the need for further development in teacher training and the provision of specialized teaching materials to support inclusive education in all schools.